2020
DOI: 10.1016/j.colcom.2020.100282
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and inexpensive method for functionalizing metallic biomaterials used in orthopedic applications

Abstract: Implantations of metallic biomaterials are being carried out more and more frequently due to accident and population aging. Therefore, there is a need for new metallic implants which can combine properties such as durability, biocompatibility and affordability. In this study, multilayer functionalized 316 L stainless steel (SS) supports resistant to steam sterilization were presented. An electropolymerization of pyrrole was performed on SS supports to obtain a protective layer. This polypyrrole coating rendere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…PPy films had a thickness of 4.98 µm ± 0.15 µm and a low roughness of 0.27 µm ± 0.05 µm. In this study, the films obtained were thicker (4.9 µm vs. 2.2 µm) than those obtained by Hamdaoui S et al [37]. These results are consistent because the Py solution used was twice as concentrated as the one previously used in the lab.…”
Section: Electrodeposition Of Ppy Coatingssupporting
confidence: 89%
“…PPy films had a thickness of 4.98 µm ± 0.15 µm and a low roughness of 0.27 µm ± 0.05 µm. In this study, the films obtained were thicker (4.9 µm vs. 2.2 µm) than those obtained by Hamdaoui S et al [37]. These results are consistent because the Py solution used was twice as concentrated as the one previously used in the lab.…”
Section: Electrodeposition Of Ppy Coatingssupporting
confidence: 89%
“…It was reported that the NaSa is predominantly an anodic inhibitor [29]. In the case of molybdate was also used extensively as a corrosion inhibitor of iron and stainless steels over a wide-ranging temperature and pH range [11,13]. The anion positively affects the passivity breakdown and pitting initiation of 316L SS.…”
Section: Corrosion Inhibition Study Of 316l Ss In Presence Of Additivesmentioning
confidence: 99%
“…They are one of the oldest and most widely used anti-inflammatory drugs and also exhibit various recognized pharmacological roles such as anticancer, neuroprotective, antipyretic, skin antiaging, and antidiabetic effects [10]. It was reported that the presence of sodium salicylate in a polypyrrole coating improves the corrosion protection of 316L SS, promoting the formation of the passive layer on the surface of substrate [11,12]. Moreover, it has been informed a favorable in vivo vascular compatibility of a salicylate-based polymer coating employed as a drug-eluting for metallic stents [13].…”
Section: Introductionmentioning
confidence: 99%
“…There is no need for surface preparation prior to EDM, and the process also converts the surface into a biocompatible oxide layer of significant thickness, increasing the biocompatibility of the substrate and creating a convenient environment for cell attachment and growth [93][94][95]. When compared to other surface modification procedures, the EDM process increases the micro-hardness, biocompatibility, wear, and corrosion resistance of implant surfaces by forming different carbides and intermetallic compounds on the coasted surface [96][97][98][99].…”
Section: Biomaterials Properties and Surface Modificationmentioning
confidence: 99%